1999
DOI: 10.1128/jb.181.9.2739-2744.1999
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Fragment of the Precursor Tail Lysozyme of Bacteriophage T4 Stays as a Structural Component of the Baseplate after Cleavage

Abstract: Tail-associated lysozyme of bacteriophage T4 (tail lysozyme), the product of gene 5 (gp 5), is an essential structural component of the hub of the phage baseplate. It is synthesized as a 63-kDa precursor, which later cleaves to form mature gp 5 with a molecular weight of 43,000. To elucidate the role of the C-terminal region of the precursor protein, gene 5 was cloned and overexpressed and the product was analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, immunoblotting, analytical ultracen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…From the CD spectra of gp5C, LisDps, and BSPS (Figure 4), the negative peaks of gp5C (216–218 nm) and LisDps (208 nm and 222 nm) suggest that the gp5C is predominantly in the β‐sheet conformation, whereas LisDps is predominantly α‐helical in conformation (Figure 4 A). These spectra agree with previous data12, 13 and are consistent with the X‐ray crystal structures 5. 8 The CD spectrum of BSPS is similar to that calculated by combining the spectrum of LisDps with that of gp5C (Figure 4 B).…”
Section: The Sizes Of Gp5c Lisdps and Self‐assembled Bsps As Determsupporting
confidence: 92%
“…From the CD spectra of gp5C, LisDps, and BSPS (Figure 4), the negative peaks of gp5C (216–218 nm) and LisDps (208 nm and 222 nm) suggest that the gp5C is predominantly in the β‐sheet conformation, whereas LisDps is predominantly α‐helical in conformation (Figure 4 A). These spectra agree with previous data12, 13 and are consistent with the X‐ray crystal structures 5. 8 The CD spectrum of BSPS is similar to that calculated by combining the spectrum of LisDps with that of gp5C (Figure 4 B).…”
Section: The Sizes Of Gp5c Lisdps and Self‐assembled Bsps As Determsupporting
confidence: 92%
“…The main structural component of the hub, (gp27) 3 (gp5) 3 , was determined by Kanamaru et al (2002). Kanamaru et al had found that gp5 undergoes maturational processing in which the peptide bond between Ser351 and Ala352 is cleaved to generate gp5* and (gp5C) 3 (Kanamaru et al 1999).…”
Section: Tail Sheath Protein Gp18mentioning
confidence: 99%
“…The expression and purification of proteins containing His 6 fragments were performed as reported previously 21. 22 The proteins were checked by SDS PAGE and MALDI‐TOF MS (Voyager instrument, PE Biosystems). All reactions were carried out at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The complexes of (gp27–gp5) 3 , (gp5) 3 , and (gp5C) 3 were overexpressed and purified with the aid of a His 6 fragment introduced onto the C terminus of gp5 as described in previous reports 21. 22 We then studied the self‐assembly of trimeric gp5 coupled with the in situ synthesis of Au nanoclusters (NCs). The three histidine‐rich regions form a triad at the C termini of (gp5–His 6 ) 3 (Figure 1 a).…”
mentioning
confidence: 99%